2018
DOI: 10.1155/2018/9328120
|View full text |Cite
|
Sign up to set email alerts
|

Pentacam HR Indices Variation in Normal Corneas with Different Corneal Thickness

Abstract: Purpose To evaluate the effect of variable corneal thickness on Pentacam HR diagnostic indices in normal corneas. Methods Retrospective study was conducted at Al Watany Eye Hospital, Cairo, Egypt. Consecutive 160 eyes of young myopic subjects without KC were evaluated using Pentacam HR (WaveLight Allegro Oculyzer II, Erlangen, Germany). The elevation- and thickness-based indices were recorded. Enrolled corneas were categorized into three groups according to TCT quartiles; group 1 (39 eyes) included corneas wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…e human eye has a very complex structure, of which the cornea, located at the very front of the eye, is composed of transparent tissue that not only protects the eye but also provides 70% of the refractive index of the eye [1] and is the main refractive medium of the human eye, which means that small changes in the morphology of the cornea can lead to significant changes in the optical properties of the whole eye. Corneal diseases such as cone keratoconus, dilatation [2], and keratoconus surgery [3] can all lead to significant changes in the optical properties of the cornea.…”
Section: Introductionmentioning
confidence: 99%
“…e human eye has a very complex structure, of which the cornea, located at the very front of the eye, is composed of transparent tissue that not only protects the eye but also provides 70% of the refractive index of the eye [1] and is the main refractive medium of the human eye, which means that small changes in the morphology of the cornea can lead to significant changes in the optical properties of the whole eye. Corneal diseases such as cone keratoconus, dilatation [2], and keratoconus surgery [3] can all lead to significant changes in the optical properties of the cornea.…”
Section: Introductionmentioning
confidence: 99%
“… 24 Roshdy et al . 7 reported higher back elevation of the thinnest point in thick corneas than thin and average ones. It contradicts our result without a significant difference between groups in terms of back and front elevations.…”
Section: Discussionmentioning
confidence: 88%
“…Roshdy et al . 7 showed that thinner corneas had a PPI-max greater than that of thicker corneas. On the contrary, ART-max increased with the increase in thickness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, BFTE has been recommended for use by other studies, as they concluded that toric ellipsoid reference surface is the most sensitive reference body to compare KC to normal corneas. Roshdy et al (10) . reported that posterior elevation from both 8mm BFS and BFTE had the highest AUROC (0.983 and 0.986, respectively).…”
Section: Discussionmentioning
confidence: 99%